The Contribution of Genre Awareness and Reading Habits Towards Students' Reading Comprehension - Andreani, Sri; Muniroh, Siti; Suharyadi, Suharyadi; Astuti, Utari Praba; Yulizar, Yulizar (Universitas Pendidikan Indonesia, 2021)
Previous studies revealed that genre awareness and reading habits partially correlate with reading comprehension. This article reported the results of a study aiming to find out the contribution of genre awareness and reading habits towards the development of students’ comprehension of reading English texts. The participants of this study were 68 students of the Department of English of a state-owned university in East Java, Indonesia, in the 2020/2021 academic year. These students took the three reading courses (Intensive Course, Basic, and Intermediate Reading courses) and were assumed to have been familiar with genres and have developed some reading habits. This research employed a correlational design, involving two predicting variables (genre awareness and reading habits), and one response variable (comprehension). The data were gathered using three instruments: an objective test to measure students’ genre awareness, an online questionnaire to identify students’ reading habits, and an objective test to measure students’ reading comprehension. The data were analyzed using multiple linear regression analysis aided by SPSS/PASW Program. The results showed that the data are normally distributed so that conclusions can be drawn accurately that genre awareness and reading habits partially and significantly contribute to reading comprehension. The results also indicated that genre awareness and reading habits simultaneously and significantly contribute to reading comprehension, as shown by the results of the analysis that genre awareness and reading habits contributed 0.203 or 20.3% to reading comprehension. The rest (79.7%) was attributed to other variables outside the variables under study. This study concludes that good genre awareness and good reading habits help students develop good reading comprehension. The results provided in this paper can be used by English teachers as an alternative to help their students improve their genre awareness and cultivate good reading habits.